The Incentive Reward Complex and the slowest U.S. post‑WW II recovery on record - Beranek, William; Kamerschen, David R. (Economics and Business Review, 2017)
Government policymakers (both Fed and U.S. Treasury) remain puzzled over the lack of vigor in the post-Great Recession recovery of 2010 to 2017, blaming it in part on a slowdown in productivity growth and the retirement of workers. But an equally plausible explanation lies in their failure to recognize the importance of the Incentive Reward Complex in providing an improved springboard for economic growth. Support for this hypothesis lies in the Fed’s data base, along with evidence that fails to support stimulus policies of both the U.S. Treasury and the Fed. Rather than more of these types of government interventions, we may need fewer of them along with more of the culture of incentives and rewards.